Female immigrant entrepreneurship: The experience of Chinese migrants to Australia - Margaret Patrickson; Leonie Hallo (Administrative Sciences, 2021)
This article reports on findings from interviews with a small group of Chinese female immigrants to Australia who have started up their own business since their arrival. Unlike most publications concerning immigration that focus upon financial factors, we have instead concentrated on their personal journeys, why they started their businesses and the benefits they sought. We interviewed thirteen participants in Adelaide who had recently arrived from China with the aim of immigrating permanently to Australia. Immigration records indicate that by 2020 this figure had risen to over 160,000 per annum. However, it dropped again quickly in 2020 following the beginning of COVID-19. Nonetheless, according to recent Australian government records, over 866,200 current Australian residents have Chinese ancestry and 74% are first-generation migrants. The primary motivators for respondents were independence and control as well as income and skill development. Respondents were also satisfied by the personal development they gained.
Keywords: 350; Chinese immigrants; control; immigrant entrepreneurship; independence; motivators for entrepreneurial start-up; personal development